Effect of reconstituted method on shear strength properties of peat - Wahab, Norhaliza (2017)
Peat is an organic soil contains more than 75% organic content. Shear strength of the soil is one of the most important parameters in engineering design, especially during the pre-construction and post-construction periods, since used to evaluate the foundation and slope stability of soil. Peat normally known as a soil that has very low shear strength and to determine and understand the shear strength of the peat is difficult in geotechnical engineering because of a few factors such as the origin of the soil, water content, organic matter and the degree of humification. The aim of this study was to determine the effective undrained shear strength properties of reconstituted peat. All the reconstituted peat samples were of the size that passing opening sieve 0.425mm, 1.000mm, 2.360mm and 3.350mm and were preconsolidated at pressures of 50 kPa, 80 kPa and 100 kPa. The relationship deviator stress- strain, σdmax and excess pore water pressure, Δu, shows that in both of reconstituted and undisturbed peat gradually increased when confining pressure, σ’ and pre- consolidation pressure, σc increased. As a conclusion, the undrained shear strength properties result obtained shows that the RS3.350 has higher strength than RS0.425, RS1.000 and RS2.360. However, the entire reconstituted peat sample shows the increment value of the shear strength with the increment of peat size and pre- consolidation pressure. For comparison purposes, the undrained shear strength properties result obtained shows that the reconstituted peat has higher strength than undisturbed peat. The factors that contributed to the higher shear strength properties in this study are segregation of peat size, pre- consolidation pressure, initial void ratio and also the physical properties such as initial water content, fiber content and liquid limit.